Temporal shifts in displacement vectors: new insights into the unprecedented Mayotte volcanic event through advanced GNSS analysis - Pirti, Atinc; Karatay, Secil (INST GEOLOGY & GEOGRAPHY, 2025)
The Mayotte seismic-volcanic crisis, initiated in May 2018, represents one of the most significant submarine magmatic events ever monitored in near real-time. This study leverages a nine-year Global Navigation Satellite System (GNSS) time series (2014-2023) from the MAYG station to investigate the temporal evolution and directional changes in ground displacement vectors associated with the event. Using both static and kinematic GNSS processing, including Precise Point Positioning with Ambiguity Resolution (PPP-AR), we identify three distinct phases of deformation: a north-eastward pre-crisis trend, an abrupt eastward shift coinciding with the peak magmatic activity (May 2018-June 2019), and a post-crisis return to north-eastward motion with diminished but ongoing subsidence. The data reveal a dramatic 20 cm vertical subsidence and significant horizontal movement indicative of deep magma withdrawal and crustal readjustment. High-resolution analyses during the initial five days of the crisis suggest a sequence of discrete magmatic pulses. Our findings provide new insights into the geophysical response of volcanic island settings to deep-seated submarine eruptions and highlight the importance of integrating advanced GNSS techniques in understanding complex crustal deformation processes.
Keywords: GNSS deformation monitoring; submarine volcanism; Mayotte seismic-volcanic crisis; displacement vector analysis; PPP-AR geodetic technique; PERFORMANCE; Geology